Democracy in the age of new media galaxy = Democracia en la era de la nueva galaxia mediática - Feenstra, Ramón A. (Veritas)
Representative democratic systems seem to be following divergent trends in recent times. On the one hand, there are certain signs of decline such as the fall in voter turnout or the increased distance between politicians and citizens. On the other hand, on occasions the public seems to be acquiring a greater political role as a result of a new media landscape that offers new opportunities for political participation. These trends have led to different interpretations of the present situation of democracy: one pointing to the decline of democracy and the other to a democratic transformation; two contrasting ways of understanding the present that challenge us to ask which of the two comes closest to providing an accurate picture of the architecture of democracy today. This paper will attempt to resolve this question by paying particular attention to the role of the new media galaxy in promoting new forms of citizens’ participation